The use of an autologous platelet-rich fibrin membrane in urethroplasty for cases of distal hypospadias - Osama Abdelazim; Khaled Salah Abdullateef; Elsayed Khedr; Mahmoud Tarek (SpringerOpen, 2024)
Abstract Background Among pediatric surgical procedures, hypospadias surgery is one of the most difficult. The most prevalent complication following hypospadias repair is urethrocutaneous fistula. Numerous procedures have been developed to prevent and resolve this issue. One such method is platelet-rich fibrin (PRF) membrane preparation, which is a straightforward process requiring only the patient's serum. It has already been utilized successfully in plastic and reconstructive surgeries, where it significantly enhances the healing capacity and decreases the risk of infections. The purpose of this study is to assess the efficacy of an autologous PRF membrane in promoting healing and reducing fistula occurrence in cases of de novo distal hypospadias. Methods Forty patients with primary distal hypospadias underwent TIP repair, as a part of a prospective controlled randomized study from April 2017 to February 2018. The cases were randomly allocated into two categories. TIP repair done in all cases by the same surgeon. Twenty cases comprised group A, which utilized a preputial or local dartos flap as an additional protective layer over the urethroplasty. In contrast, group B comprised 20 cases in which the urethroplasty was covered with a PRF membrane. The initial follow-up duration was 6 months. Each group's fistula incidence and other associated complications were documented. Results Two groups were compared during the initial 6-month follow-up period. There were seven cases of urethrocutaneous fistula in group A, representing a 35% incidence rate. In group B, there were two cases that had fistula with an incidence of 10% in the early postoperative period. Two patients (10%) in group A developed meatal stenosis and only one patient in group B (5%) developed meatal stenosis. Glandular dehiscence occurred in one patient (5%) in group B. There was no skin wound infection in both groups. Conclusion The PRF membrane may be a promising method as a coverage layer over the urethroplasty aiming to reduce the fistula rate after the repair. A larger comparative study is needed to evaluate the efficacy of PRF membranes in promoting wound healing.